Theoretical and applied tools using for optimization investment and construction projects - TUGAY, Aleksei; DVORNICHEN, Ihor; OLIINYK, Valerii; ZYAKHOR, Dmitry; MOLODKO, Oleksii (Ways to Improve Construction Efficiency, 2024)
The article provides for the possibility of using theoretical and applied tools for optimization of investment and construction projects. The use of innovative methods through an engineering approach to the organization of construction consists in accumulating the results of scientific achievements, knowledge, careful study of external factors in order to find new ideas, new technologies and tools, which should contribute to obtaining better results in the implementation of construction projects throughout their entire life cycle, and also minimize risks for the investor. The analysis conducted allowed to identify the need for improving methods for assessing the reliability and optimizing the successful implementation of construction projects. This is especially relevant in conditions when increasing the efficiency of capital investments in construction projects requires improving economic relations in construction, strengthening contractual discipline, increasing the economic responsibility of builders and customers for the final results. For the effective use, in the current economic conditions, of existing methods of construction planning and production organization, for a positive impact on the acceleration and efficiency of construction, it is necessary to include in these methods the consideration of the existing specific features of the construction industry. The options for the possible application of organizational and technological tools are considered, the results of the presented material can be used to solve practical problems of optimizing and improving project indicators in planning and managing investment and construction activity processes. A professional approach to the tool for effectively solving the problems of developing construction production with optimal distribution of investments is an obvious necessity today. The need to create methods for solving problems related to increasing the efficiency of construction project implementation, minimizing project execution time, and maximizing profits, taking into account organizational, technological, economic factors and elements of the external environment, determines the relevance of this work.